Dietary co-exposure to methylmercury and monosodium glutamate disrupts cellular and behavioral responses in the lobster cockroach, Nauphoeta cinerea model (2018)
The present study aims to investigate the effect of monosodium glutamate (MSG) both separately and combined with a low dose of methylmercury (MeHg) on behavioral and biochemical parameters in Nauphoeta cinerea (lobster cockroach). Cockroaches were fed with the basal diet alone, basal diet + 2% NaCl, basal diet + 2% MSG; basal diet+0.125 mg/g MeHg, basal diet+0.125 mg/g MeHg + 2% NaCl; and basal diet+0.125 mg/g MeHg + 2% MSG for 21 days. Behavioral parameters such as distance traveled, immobility and turn angle were automatically measured using ANY-maze video tracking software (Stoelting, CO, USA). Biochemical end-points such as acetylcholinesterase (AChE), glutathione-S-transferase (GST), total thiol and TBARS were also evaluated. Results show that MeHg+NaCl, increased distance traveled while MeHg+MSG increased time immobile. AChE activity was significantly reduced in cockroaches across all the groups when compared to the control. There was no significant alteration in GST activity and total thiol levels. It could be that both NaCl and MSG potentiates the neurotoxic effect of MeHg in cockroaches.